2021
DOI: 10.1016/j.asmr.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Injection of Bone Marrow Aspirate for Glenohumeral Joint Osteoarthritis: A Pilot Randomized Control Trial

Abstract: Purpose: To compare the efficacy of a single, intra-articular, nonconcentrated bone marrow aspirate (BMA) injection in comparison to cortisone for the treatment of glenohumeral joint osteoarthritis (GHJ OA). Methods: Inclusion criteria were patients between the ages of 18 and 75 with a diagnosis of GHJ OA on radiograph. Patients were randomized to receive an ultrasound-guided, intra-articular cortisone injection or BMA injection (without concentration). The primary outcome measure was the Western Ontario Osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…8 In a pilot clinical trial, individuals with GHOA received either a corticosteroid or an injection of BMA. 40 Results indicated that at the 12-month follow-up, individuals treated with BMA had greater improvements in function and pain, suggesting a superiority of BMA compared to a corticosteroid injection. 40 With regard to adipose-derived orthobiologics, autologous non-digested microfragmented adipose was used to treat patients with GHOA in two cohort studies.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…8 In a pilot clinical trial, individuals with GHOA received either a corticosteroid or an injection of BMA. 40 Results indicated that at the 12-month follow-up, individuals treated with BMA had greater improvements in function and pain, suggesting a superiority of BMA compared to a corticosteroid injection. 40 With regard to adipose-derived orthobiologics, autologous non-digested microfragmented adipose was used to treat patients with GHOA in two cohort studies.…”
Section: Discussionmentioning
confidence: 94%
“…40 Results indicated that at the 12-month follow-up, individuals treated with BMA had greater improvements in function and pain, suggesting a superiority of BMA compared to a corticosteroid injection. 40 With regard to adipose-derived orthobiologics, autologous non-digested microfragmented adipose was used to treat patients with GHOA in two cohort studies. 23,41 In one study, patients with mild to moderate GHOA received one injection of microfragmented adipose.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This volume is small enough such that the draw is not diluted with peripheral blood [ 33 , 34 ], but entails a sufficient volume to treat knee OA as has been done in a previous studies [ 30 ]. Previous studies have used between 6 and 20 mls of BMA or BMC [ 13 , 37 ], although previous research using the MC system has found that roughly 10 mls of BMA using this technique is sufficient to achieve positive outcomes [ 30 , 38 ]. To inject the BMA, the patient was placed supine and sterilizing the skin of the knee to be treated was sterilized.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have used between 6 and 20 mls of BMA or BMC [13,37], although previous research using the MC system has found that roughly 10 mls of BMA using this technique is sufficient to achieve positive outcomes [30,38]. To inject the BMA, the patient was placed supine and sterilizing the skin of the knee to be treated was sterilized.…”
Section: Bone Marrow Aspiration and Injectionmentioning
confidence: 99%